Mediación y Construcción de Sentidos: notas en torno a su articulación teórico-metodológica en el estudio de la apropiación de Internet - Alonso Alonso, María Margarita (Mediaciones Sociales, 2010)
The mediation paradigm has provided a theoretical basis for empirical research on the reception and appropriation of media. The symbiosis between reception and mediation in the field of communication studies has been an epistemological axis of contemporary studies that seek to analyze the social production of meaning. The merit of the above described interdependence lies in the combination between an essentially methodological research strategy and a theoretical and conceptual exploration proposal. This paper makes a brief analysis of the evolution of the binomial Mediation-Construction of Meaning, to later characterize the renewal of this connection based on recent theoretical and methodological approaches by Latin American researchers, from which is integrated through the grounded theory method, a conceptual model for the study of Socio-Cultural Appropriation and Use of the Internet.
Keywords: Mediation; Construction of meaning; Uses; Appropriation; Internet